Microbial production of xylanase using Regional Agro wastes - SHABEENA ANJUM K S; RAVI M; Y M JAYARAJ (International Journal of Pharma and Bio Sciences, 2017)
Currently, xylanases, which is responsible for hydrolysis of xylan, the major hemicelluloses of plant cell wall, have received great attention in the development of environmental friendly technologies. For efficient and significant production of xylanolytic enzymes, choice of an appropriate inducing substrate and the best potential medium composition are considered. In the current study, we purified and characterized the isolated xylanase activity and in addition, we investigated the effect of different additives on xylanase stability. The biomass production of the fungi was higher throughout the incubation period when wheat bran is used as the substrate as compared with the other substrates including orange-peel, wheat bran, sugarcane, oats and rice bran. Though the enzyme activity was higher with wheat bran as compared with the other substrates throughout the incubation period, its activity is was highest on 9th day of incubation period with the gradual decline in its activity on 11th day. It has been observed that the activity of xylanase from Aspergillus Niger was most favorable at 30◦C and it declined at 40◦C. In case of xylanase purified from Bacillus arseniciselenatis DSM 15340, the enzyme activity was found to be most favorable at 50◦C and significantly declined at 80◦C. Using agro residual substrate like wheat bran; Aspergillus Niger produced xylanase in significant amount when grown on solid state conditions. Considering the optimum conditions that are required for the production of xylanase, potentially it can be used for large-scale production by using wheat bran as the substrate.